Academic Performance of College Students With and Without Disabilities: An Archival Study - Jorgensen, Shirley; Fichten, Catherine S.; Havel, Alice; Lamb, Daniel; James, Crystal; Barile, Maria (Canadian Journal of Counselling and Psychotherapy, 2007)
The academic outcomes of students with (n = 653) and without disabilities (n = 41,357) were compared over a 12-year period at a large Quebec College. Results showed that students with and without disabilities, including learning disabilities, had virtually identical grades and graduation outcomes. However, students with disabilities undertook lighter course loads and took approximately one semester longer to graduate. The findings suggest that counsellors need to urge students with disabilities to consider higher education when developing their career plans. In planning the transition, students need to be made aware of disability-related services at post-secondary institutions.